The Influence of Block Ionomer Microstructure on Polyplex Properties: Can Simulations Help to Understand Differences in Transfection Efficiency?. Issue 17 (24th February 2017) - Heller, Philipp; Zhou, Jiajia; Weber, Benjamin; Hobernik, Dominika; Bros, Matthias; Schmid, Friederike; Barz, Matthias
Abstract : Gene therapies enable therapeutic interventions at gene transcription and translation level, providing enormous potential to improve standards of care for multiple diseases. Nonviral transfection agents and in particular polyplexes based on block ionomers are—besides viral vectors and cationic lipid formulations—among the most promising systems for this purpose. Block ionomers combine a hydrophilic noncharged block, e.g., polyethylene glycol (PEG), with a hydrophilic cationic block. For efficient transfection, however, endosomolytic moieties, e.g., imidazoles, are additionally required to facilitate endosomal escape, which raises the general question how to distribute these functionalities within the block copolymer. Combining molecular dynamics simulation with physicochemical and biological characterization, this work aims to provide a first rational for the influence of block ionomer microstructure on polyplex properties, e.g., size, shape, and transfection efficiency. Our findings underline that a triblock microstructure is most efficient in compacting pDNA, which reduces polyplex size, enhances stability against degradation by DNase I, and thus provides better transfection performance. Abstract : Combining molecular dynamics simulation with physicochemical and biological characterization, this work aims to provide a first rational for the influence of block ionomer microstructure on polyplex properties, e.g., size, shape, and transfection efficiency.